2002
DOI: 10.1073/pnas.252618999
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibitors promote differentiation of insulin-producing tissue from embryonic stem cells

Abstract: The use of embryonic stem cells for cell-replacement therapy in diseases like diabetes mellitus requires methods to control the development of multipotent cells. We report that treatment of mouse embryonic stem cells with inhibitors of phosphoinositide 3-kinase, an essential intracellular signaling regulator, produced cells that resembled pancreatic ␤ cells in several ways. These cells aggregated in structures similar, but not identical, to pancreatic islets of Langerhans, produced insulin at levels far greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
302
3
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(322 citation statements)
references
References 31 publications
9
302
3
8
Order By: Relevance
“…It has been shown that pancreatic cell types can be generated from mouse and non-human primate ESCs [10][11][12][13][14][15][16][17][18]. Based on these findings, recent studies have also suggested the potential of hESCs to differentiate into insulin-producing cells through spontaneous in vitro differentiation [5] or the use of a multi-stage protocol [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that pancreatic cell types can be generated from mouse and non-human primate ESCs [10][11][12][13][14][15][16][17][18]. Based on these findings, recent studies have also suggested the potential of hESCs to differentiate into insulin-producing cells through spontaneous in vitro differentiation [5] or the use of a multi-stage protocol [6].…”
Section: Introductionmentioning
confidence: 99%
“…Boyd et al (2008) compared three different protocols to differentiate ESCs into IPCs using the embryoid body formation strategy. This study indicated that the IPCs generated using Blyszczuk protocol (Blyszczuk et al 2004) exhibited superior C-peptide expression and longer normoglycemic rescue in diabetic mice when compared with the Hori's and Lumelsky's protocols (Hori et al 2002;Lumelsky et al 2001). In protocol described by Blyszczuk the ESCs were cultured in ''handing drops'' and in suspension for 5 days to form embryoid bodies.…”
Section: Differentiation Of Embryonic Stem Cellsmentioning
confidence: 99%
“…The Lumelsky's protocol involves serum-free ITSFn medium and basic fibroblast growth factor (bFGF) treatments (Lumelsky et al 2001). The Hori's protocol involves additionally treatment of differentiating cells with PI3 kinase inhibitor LY294002, but excludes B27 supplement (Hori et al 2002). Real-time polymerase chain reaction and immunofluorescence techniques indicated that each of these protocols lead to differentiation of ESCs toward pancreatic lineage.…”
Section: Differentiation Of Embryonic Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations